Utilization of Edmodo as Part of Optimization Learning in Network - Turmini Turmini; Nurhayati Nurhayati; Happy Fitria (Universitas Bengkulu, 2019)
Edmodo is a form of learning application used by academics in order to carry out online learning. This research was conducted with the aim of informing more widely about Edmodo and describing how to use it to be able to optimize online learning. The research method used is a qualitative research method with a type of literature study. The results of the research conducted are that Edmodo has provided complete facilities in the context of implementing virtual learning. Intended as virtual learning because the learning process is carried out in the network. Educators (teachers / lecturers) have breadth in the implementation of classroom management because students can be made classes as classes in conventional learning. Educators can optimize the dissemination of information as well as in applications that have provided many features to make tests with various types of tests offered, educators can also provide assignments with predetermined collection times so as to optimize classroom management, educators can provide a direct assessment of the assignments students, giving awards with various types of awards. The advantage of using Edmodo is that there is no limit on space and time in learning because at any time it can take part in learning, it does not depend on the presence of educators in front of the class because wherever educators can still provide optimal learning.